Biological characterization of an isolate of Cotton leaf curl Rajasthan virus from northern India and identification of sources of resistance - and A. VARMA*, G. RADHAKRISHNAN, V.G. MALATHI (Indian Phytopathology, 2004)
An isolate of Cotton leaf curl Rajasthan virus (CLCuRV), a Begomovirus, from Sri Ganganagar, the major cotton growing area in North-West India, was characterized at biological level. The virus could be transmitted by whitefly (Bemisia tabaci) when given a minimum acquisition and inoculation access period of 30 min and 10 min, respectively. B. tabaci could transmit the virus efficiently from Gossypium hirsutum to G. hirsutum, G. barbadense and seven other species belonging to families Fabaceae, Malvaceae and Solanaceae. All the infected plants developed typical leaf vein thickening and curling characteristic of CLCuRV infection. The virus could be back inoculated from these hosts to G. hirsutum cv. LH 900. To identify sources of resistance to CLCuRV, 126 genotypes of G. hirsutum, 19 of G. barbadense, 14 of G. arboreum and two of G. herbaceum were tested against CLCuRV by whitefly inoculation. All the genotypes of G. arboreum and G. herbaceum were found to be highly resistant (no infection) whereas all the genotypes of G. barbadense were highly susceptible (100% infection); 62 genotypes of G. hirsutum were highly resistant, 5 highly susceptible and the remaining showed varying degree of resistance.